2017
DOI: 10.3892/ol.2017.7718
|View full text |Cite
|
Sign up to set email alerts
|

MED28 increases the colony‑forming ability of breast cancer cells by stabilizing the ZNF224 protein upon DNA damage

Abstract: Abstract. The regulation of gene expression by transcription factors serves a critical function in cell proliferation. Zinc-finger protein 224 (ZNF224), a Krüppel-associated-box-containing zinc finger protein, is known to serve a crucial function in integrating the transcriptional co-factors that activate transcriptional regulation pathways in the cell. A previous study demonstrated that ZNF224 enhances cell proliferation by downregulating the expression of p21 and p53. The present study identified mediator co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Recent studies indicate that the overexpression of MED28 induces cancer cell proliferation and increases the colony-forming ability of cancer cells upon DNA damage [11,13]. In this study, we first identified four transcription factors, namely E2F-1, NRF-1, ETS-1, and C/EBPβ, which increase the expression level of MED28 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recent studies indicate that the overexpression of MED28 induces cancer cell proliferation and increases the colony-forming ability of cancer cells upon DNA damage [11,13]. In this study, we first identified four transcription factors, namely E2F-1, NRF-1, ETS-1, and C/EBPβ, which increase the expression level of MED28 .…”
Section: Discussionmentioning
confidence: 95%
“…MED28 is highly expressed in breast, colon, and prostate cancers, and MED28 induces cancer cell proliferation via the mitogen-activated protein kinase kinase-1 (MAP2K1) signaling pathway [10,11,12]. Recently, we reported that the interplay between MED28 and ZNF224, a Krüppel-associated-box-containing zinc finger protein transcriptional cofactor, was associated with cancer cell proliferation upon initiation of the DNA damage response [13]. A study in knockout mice has shown that the genetic deletion of MED28 results in peri-implantation embryonic lethality by reducing the expression of OCT4 and NANOG, which are pluripotency transcription factors [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the tested KRAB-ZNFs, numerous studies demonstrate significant engagement of ZNF224 in the regulation of cancer development and progression, especially in melanoma [ 37 ], breast cancer [ 38 , 39 ], and Wilms tumor [ 40 ]. However, the data for clear cell kidney carcinoma are still missing.…”
Section: Discussionmentioning
confidence: 99%
“…To reveal the molecular mechanism underlying the ecological adaptation of Sillago species, we estimated the dN/dS to identify the PSGs of Sillago species. A total of 44 orthologous genes were identified to be positively selected and might be involved in many biological processes, including the stress response (LTV1 [44], SMO [45], PSA [46,47], ABCB7 [48], UBIAD1 [49], COPA [50], MED27 [51,52], MED28 [51,52], SF3A1 [53], SF3B5 [53], TFIP11 [54], NUDT6 [55], POLλ [56], and DEPDC5 [57]), energy metabolism (APF [58] and IMMT [59]), carbohydrate metabolism (SUCLG1 [60]), amino acid metabolism (GCN4 [61] and CPD [62]), lipid metabolism (HUWE1 [63] and FABZ [64]), visual sense (AP4B1 [65] and PRPF8 [66]), growth and differentiation (ABTB1 [67], UBE4A [68], DOHH [69], and GAB1 [70]), embryogenesis (SBDS [71], TAF5L [72], and SEC8 [73]), and others.…”
Section: Positively Selected Genes Might Contribute To the Ecologicalmentioning
confidence: 99%